Evolved NWDAF Towards a Fully Distributed Artificial Intelligence in the 6G Network Architecture - Souza Neto, Natal Vieira de; Gonçalves, Maurício Amaral; Oliveira, Daniel Ricardo Cunha; Molinos, Diego Nunes; Moreira, Rodrigo; Silva, Flávio de Oliveira (Anais do Workshop de Redes 6G (W6G); 2024: Anais do IV Workshop de Redes 6G, 2024)
Artificial Intelligence (AI) is essential for evolving mobile networks towards 6G technology generation and beyond. In this context, the 3GPP has incorporated the Network Data Analytics Function (NWDAF) at the network’s core to leverage network data analytics, focusing on using analytics for automation. However, although NWDAF represents a significant advancement in this area, there is no consensus on deploying AI in the 6G network. This work suggests a framework for developing NWDAF that includes the necessary interfaces and behaviors to enhance the core network with AI capabilities Beyond 5G (B5G) and 6G networks. By analyzing existing literature, we identify a set of potential research directions and propose and suggest a hybrid approach to integrate AI across the entire network using a new distributed network function called Evolved Network Data Analytics Function (eNWDAF).